Daya Dukung Kawasan Wisata Di Pantai Sanur, Denpasar, Bali - Saputra, Agus Widia Cesa; Putra, I Dewa Nyoman Nurweda; Puspitha, Ni Luh Putu Ria (Journal of Marine Research and Technology, 2025)
Sanur Beach is one of the many natural tourist attractions in Province of Bali, currently focusing on economic benefits without considering environmental impacts. Proper management is needed for sustainable utilization. This study aimed to determine the appropriate zoning Carrying Capacity (CC) for Sanur Beach. The research used purposive sampling, dividing the area into two points based on beach land use variations. The method was descriptive, with quantitative and qualitative data collected through field measurements and interviews. At least 58 respondents were surveyed, and most provided positive feedback on various aspects affecting their tourist experience. However, improvements are needed in seating, electricity, trash bins, and parking facilities. The carrying capacity of Sanur Beach was based on the area and the time available for activities each day. Sanur Beach has a recreational area of 4.83 hectares and can accommodate 3.882 people daily. The total CC for the entire Sanur Beach area (48,380 m² / 4.83 ha) is 7.740,8 people daily. This capacity is assumed sufficient to cover the average daily visitor count of around 3.882 people. Sanur Beach is zoned into three areas: recreation, swimming, and fishing. This study provides guidelines for better management to ensure sustainability and visitor safety.